IMPLEMENTASI ARM MANIPULATOR DAN SENSOR WARNA DALAM PROTOTYPE OTOMATISASI SISTEM PENYORTIR BOX BERWARNA BERBASIS MIKROKONTROLLER AVR ATMEGA 8535 - Wibowo, Roby Adi; Subali, Subali (Gema Teknologi, 2013)
Roby Adi Wibowo, Subali, in paper implementation of ARM manipulator and color sensor in prototype of color box sorter automation system based on microcontroller AVR ATMega 8535 explain that the rapid development of technology at all times encourage people to overcome problems that arise around it. With a view to facilitate the work and time efficiency. Included in the field of automation control systems in a work process. One of these systems automation in sorting colored box, so that a product can be separated from one another and in accordance with the qualifications color. In this final task will be made a colored box sorter automation system using the color sensor as a detector and a manipulator arm actuator to take the box to place each color. Â  Keywords; Arm manipulator, colours sensor